DESCRIPTION OF THE IMAGE OF THE CHILD IN J. PENHALL’S DRAMAS - Akhmedova Mehrinigor Bahodirovna; Nizomova Aziza (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the description of the child’s image used in dramas of Penhall. The image of the child is a recurring theme that holds significant meaning in the dramas of J. Penhall. Through his creative works, the playwright explores various aspects of childhood and present nuanced perspectives on the experiences, challenges, and complexities faced by children. In his respective plays, Penhall delves deep into the psychological, emotional, and social dimensions of children in order to evoke a compelling portrayal of their innocence, vulnerability, curiosity, and resilience.